Chapter Extension, ramification, temporalité et dangerosité d'un grand réseau, situant Raguse (Dubrovnik) au point nodal des échanges entre la Péninsule Ibérique et l'Orient méditerranéen (XIII-XV siècle) - Fejic, Nenad (Atti delle «Settimane di Studi» e altri Convegni, 2019)
The Ragusan maritime network gradually developed from the ancient Venetian one, at the time of Venetian preponderance (1205-1358). But, at the end of the Venetian domination, the Ragusan network developed some characteristics of its own, presented in this contribution. The characteristics of the network are here presented through its four mains aspects: extension, ramification, temporality and dangerousness. In terms of extension, both in the East and in the West of the Mediterranean, the Ragusan maritime network had great similarities with the Venetian one. It is in terms of ramification, that the differences gradually appear.